Group response to social perturbation: impacts of isotocin and the social landscape. (July 2015) - Hellmann, Jennifer K.; Reddon, Adam R.; Ligocki, Isaac Y.; O'Connor, Constance M.; Garvy, Kelly A.; Marsh-Rollo, Susan E.; Hamilton, Ian M.; Balshine, Sigal
Abstract : Conflict is an inherent part of group living, and the mediation of conflict is essential for the stability of social groups. Response to within-group social conflict should depend on the external social environment. Individuals in dense social neighbourhoods have greater opportunities to disperse and join a nearby group compared to individuals in sparse social neighbourhoods with few nearby groups. To explore the influence of the social neighbourhood on responses to conflict, we experimentally perturbed groups of wild Neolamprologus pulcher, a cooperatively breeding cichlid fish, by temporarily removing a subordinate individual. Such removals typically increase the amount of within-group aggression. As predicted, aggression towards the returning subordinate and the rate of eviction from the group increased with the density of neighbouring social groups. Furthermore, we predicted that the returning subordinate could improve its likelihood of reacceptance into the group by displaying submissively. To test this prediction, we attempted to manipulate submissive behaviour by injecting the removed individuals with isotocin, a nonapeptide hormone that has been shown in the laboratory to increase the expression of submissive behaviour in this species. As predicted, subordinates that received isotocin showed more submission when returned to their group. However, contrary to our prediction, these isotocin-treated fish received more aggression from their group-mates and were more likely to be evicted than fish receiving a saline control injection. Our results emphasize the importance of the social neighbourhood in determining within-group dynamics but surprisingly contradict the notion that submissive behaviour reduces aggression and facilitates group stability. Highlights: We induced conflict in fish social groups by temporarily removing a group member. Aggression towards the returning group member increased with social density. An injection of isotocin increased submissive behaviour. Isotocin-treated fish received more aggression and were more likely to be evicted.